1997
DOI: 10.1021/la960981m
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tail−Tail Interactions versus Head-Group/Subphase Interactions in the Pressure−Area Isotherms of Fatty Amines at the Air−Water Interface. 1. Influence of Subphase Acid Counterions

Abstract: The pressure−area isotherms obtained in the initial stages after the spreading of fatty primary amines on the aqueous subphase has been investigated as a function of pH, length of hydrocarbon chain, basicity of the amine, nature of the acid counterion, etc. The main emphasis is on the high-area liquidlike features observed prominently at low pH. The dependence on the specific nature of the acid counteranion or the nature of the amine (aliphatic or aromatic) highlights the importance of the interactions at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…More importantly, the shift of the LE-LC phase transition to smaller temperatures when the molecular heads carry an ion is in qualitative agreement with the experimental observations of fatty acid monolayer with ionic head groups [45]. We also calculated two isotherms at T = 1.5 and T = 0.5 for two system sizes N = 144 and N = 256 and found that their behavior looks very similar to the experimental isotherms [45,64,65]. From these isotherms we calculated the variation ranges of the monolayer's area compression modulus and encountered that they are consistent with the experimental values reported in Refs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…More importantly, the shift of the LE-LC phase transition to smaller temperatures when the molecular heads carry an ion is in qualitative agreement with the experimental observations of fatty acid monolayer with ionic head groups [45]. We also calculated two isotherms at T = 1.5 and T = 0.5 for two system sizes N = 144 and N = 256 and found that their behavior looks very similar to the experimental isotherms [45,64,65]. From these isotherms we calculated the variation ranges of the monolayer's area compression modulus and encountered that they are consistent with the experimental values reported in Refs.…”
Section: Discussionsupporting
confidence: 85%
“…These isotherms correspond to a monolayer with ionic molecular heads and were calculated for two system sizes, one with 144 (•) and the other with 256 (•) molecules. Their behavior looks very similar to the experimental isotherms: as pressure decreases the area per molecule increases and the higher the temperature the larger the area per molecule [45,64,65]. Note that at these two temperatures there appears to be no signature of a Surface-pressure-versus-area-per-molecule isotherms for a monolayer with ionic molecular heads for systems with 144 and 256 molecules at T * = 0.5 and T * = 1.5.…”
Section: Isotherms and Compressibility Modulussupporting
confidence: 69%
“…For pure ODA monolayer, the collapse surface pressure (60 mN m À1 ) and the limiting area (about 17 Å 2 molecule À1 ) are consistent with most values found in the literature [43][44][45] while other authors provide higher values under the same conditions [40,47,49]. This size is smaller than the corresponding value of a carbohydrate amphiphilic chain ($20 Å 2 molecule À1 ) and this difference is usually attributed to mass transfer to the aqueous subphase [39].…”
Section: Oda Monolayers At the Air-water Interfacesupporting
confidence: 88%
“…Moreover, anchoring of DNA in a Langmuir-Blodgett film has made possible its immobilization [34][35][36] and the construction of DNA chips [37]. Most of these studies were developed at a lipidic interface, while surface behavior of fatty amines [38][39][40][41][42] has received few research efforts compared with other lipidic matrices. However, fatty amines provide a positive charge below its pK value (around 11 for most soluble primary amines) that is suitable for many specific molecular architectures such us Langmuir-Blodgett preparation of anionic compounds as adsorption layer [43].…”
Section: Introductionmentioning
confidence: 99%
“…Primary alkylammoniums, such as octadecylammonium (ODA), and alkylamines are compounds frequently used for monolayer studies on water [1][2][3][4][5][6][7] and for the preparation of hydrophobic clay minerals. [7][8][9][10] It is implicitly assumed that these compounds remain chemically stable during the experiment.…”
mentioning
confidence: 99%